Knowledge, Attitude, and Practice Toward Mask-Wearing Behaviors During Covid-19 Pandemic Among Mangalore Residents: A Cross-Sectional Study - Krishna, Nidhish; Ramesh, Athul; Hegde, Amitha M. (Journal of Health and Allied Sciences NU, 2022)
Objectives The objective of this study is to assess the knowledge, awareness, and practice toward mask-wearing behaviors of Mangalore residents during the coronavirus disease 2019 (COVID-19) outbreak.Materials and Methods This survey was conducted at A B Shetty Memorial Institute of Dental Sciences in Mangalore. The questionnaire consisted of 18 questions that were prepared as an online form (Google Forms), and a total of 172 responses were received among the residents of Mangalore who visited the hospital.The questions were distributed based on knowledge, attitude, and practice regarding the mask-wearing behaviors, and the distribution of responses was presented as frequency and percentages. Prior to the inception of the study, the nature and purpose of the study were explained to each respondent, and informed consent was obtained by all participants in this study.Statistical analysis was done using SPSS software version 23.Results It was evident that the COVID-19 knowledge scores were found to be significantly associated with a lower likelihood of negative attitudes and potentially dangerous practices toward the COVID-19 epidemic in this study. These findings clearly indicate the importance of improving residents' COVID-19 knowledge via health education, which may also result in improvements in their attitudes and practices toward COVID-19.Conclusion In summary, our findings suggest that Mangalore residents have fair knowledge and optimistic attitudes, despite the current lockdown measures undertaken during the second wave of COVID-19, The positivity rate in Mangalore has not reduced satisfactorily. Self-protection, testing, and vaccination would help to reduce the spread and mortality rate due to coronavirus. The residents of Mangalore should abide by the COVID -19 preventive measures and implement this knowledge into their daily practices.
Keywords: attitude; COVID-19; knowledge; Mangalore residents